A prototype system for the hydrothermal oxidation of feces. (1st December 2022) - Affolter, Joël; Brunner, Thomas; Hagger, Nicola; Vogel, Frédéric
Abstract : A stand-alone prototype SCWO system to treat fecal sludge was built. Carbon conversions over 97% were achieved during reaction times of 600 s. The prototype was operated in a cyclic and thermally almost self-sufficient mode. An ignition phenomenon was observed and explained theoretically. Graphical abstract: Abstract: To ensure access to safe sanitation facilities in rural communities, cheap off-grid technologies need to be developed to substitute pit latrines and open defecation. In this study, we present a prototype system based on hydrothermal oxidation, which, under optimal conditions, converts a fecal sludge simulant almost completely to CO 2 and water, leaving behind only a carbon-poor aqueous phase with the minerals. The prototype has been designed to process the feces from two households. This technology does not only enable a fast and complete conversion, but is potentially also very energy efficient, as the feed does not require any pre-treatment or drying. The system was found to effectively remove 97–99% of the total organic carbon within a reaction time of 600 s under an external energy demand of roughly 4 kWh per kilogram of wet feces by using the oxygen in air as an oxidant. A total of ten experiments with varying injection pressure, total solids content of the feed, and residence time in the reactor were performed to find experimental settings with high conversion. Only when the residence time was decreased from 600 to 300 s did the conversion fall significantly below 97%. To reach a target value of 99.9% TOC conversion, the reactor temperature and/or the residence time must be increased further. To achieve a system applicable in regions with no connection to the energy grid, the thermal loss of the reactor insulation needs to be lowered further to achieve an overall thermally self-sustaining operation.